2005
DOI: 10.1002/jcb.20698
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin blocks activation of pancreatic stellate cells

Abstract: Activated pancreatic stellate cells (PSCs) play a pivotal role in the pathogenesis of pancreatic fibrosis and inflammation. Inhibition of activation and cell functions of PSCs is a potential target for the treatment of pancreatic fibrosis and inflammation. The polyphenol compound curcumin is the yellow pigment in curry, and has anti-inflammatory and anti-fibrotic properties. We here evaluated the effects of curcumin on the activation and cell functions of PSCs. PSCs were isolated from rat pancreas tissue and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 48 publications
4
62
0
Order By: Relevance
“…These findings agree with the previous study showing that DPI inhibited angiotensin II-induced activation of ERK, JNK, p38 MAPK, and AP-1 in hepatic stellate cells (6). Although it is possible that NF-B is regulated by ROS-generating system that is not inhibited by DPI in PSCs, the failure of NF-B inhibition agrees with our previous findings in PSCs that antioxidant polyphenols failed to inhibit NF-B activation (29,30). It has been recognized that redoxdependent activation of NF-B is cell and stimulus specific, as opposed to the concept that oxidative stress is a common mediator of diverse NF-B activators (18,24).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings agree with the previous study showing that DPI inhibited angiotensin II-induced activation of ERK, JNK, p38 MAPK, and AP-1 in hepatic stellate cells (6). Although it is possible that NF-B is regulated by ROS-generating system that is not inhibited by DPI in PSCs, the failure of NF-B inhibition agrees with our previous findings in PSCs that antioxidant polyphenols failed to inhibit NF-B activation (29,30). It has been recognized that redoxdependent activation of NF-B is cell and stimulus specific, as opposed to the concept that oxidative stress is a common mediator of diverse NF-B activators (18,24).…”
Section: Discussionsupporting
confidence: 93%
“…DPI did not affect IL-1-induced degradation of IB-␣ (data not shown), further supporting the notion that DPI did not inhibit NF-B activation. It has been shown that activation of MAPKs plays a key role in the PDGF-induced proliferation and IL-1-induced chemokine production in PSCs (25,29,30). DPI inhibited IL-1␤-and PDGF-induced activation of ERK, JNK, and p38 MAPK (Fig.…”
Section: Cytokines and Growth Factors Induced Ros Production Through mentioning
confidence: 85%
See 1 more Smart Citation
“…It has been shown that antioxidants including plant polyphenols inhibited the activation and cell functions in PSCs both in vitro and in vivo [15,51,[84][85][86][87][88][89][90][91]. For example, ethanol-or acetaldehyde-induced collagen production was inhibited by antioxidants such as vitamin E and N-acetly-cysteine [15,51].…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Similarly, epigallocatechin-3-gallate inhibited pressure-induced a-SMA expression, type I collagen production, TGF-b1 production, and transformation to a myofibroblast-like phenotype [85]. Other plant polyphenols, such as ellagic acid and curcumin, inhibited the proliferation, MCP-1 production, collagen expression, a-SMA expression, and transformation to myofibroblastlike cells [86,87]. Ellagic acid was shown to inhibit the development of pancreatic fibrosis in vivo in male WBN/ Kob rats [88].…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%